Allelopathic effects of aqueous extracts of olax subscorpioidea oliv. on seed germination and growth of okra (abelmoschus esculentus (l.) moench) in Ibadan, Nigeria (2022)
Allelochemicals are being explored as environmentally friendly options in weed management and crop yield improvement as opposed to use of synthetic pesticides which have serious environmental damages. Allelopathic effects of aqueous extracts of different parts of Olax subscorpioidea on Okra seed germination in Petri-dish bioassays and okra performance in pot experiment were conducted in the Department of Crop Protection and Environmental Biology, University of Ibadan using a complete randomized design (CRD) and with treatments replicated five times. Ten okra seeds in three replicates were treated in separate petri-dishes with 2 ml water extracts of stem, leaf, fruit, bark and root of Olax subscorpioidea, and 2 ml distilled water (control) in two trials. Pot trials was carried out using okra seedlings with treated with 100 ml extracts at seven days intervals. Data were collected on number of germinated seeds daily and lengths of five randomly selected plumules and radicles at 7 days after sowing (DAS). Number of leaves, plant height, root and shoot dry weight of seedlings were also measured using standard methods. Data were analyzed by analysis of variance. Statistically significant (P<0.05) means were separated using Duncan’s Multiple Range Test. Leaf extract had the highest concentrations of phenolic, flavonoid and saponin compounds compared, while the stem extract had the least metabolite concentrations. Leaf extracts exerted highest inhibition on okra germination at 2 and 7 DAS in the first trial and at 7 DAS in the second trial compared to the bark, stem, root and fruit extracts of Olax subscorpioidea. The seedling growth and yield parameters in treatment extracts were better than control. In conclusion, Olax subscorpioidea has allelopathic potential with effects on germination and seedling growth of okra. It can be used as an alternative bioherbicide. Its production and agricultural potentials should be promoted.